A case of postmenopausal bleeding with an unusual finding - Rudra, Samar; Thakur, Manasi Mukund (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Authors report the case of a 55-year-old patient who presented with postmenopausal bleeding. On clinical evaluation uterus was 12 weeks size with a left sided adnexal cystic mass of 8 × 6 cm size. Further imaging studies revealed uterus size of 11.5 × 6.7 × 6.3 cm, left ovarian mass of size 8.4 × 6.7 × 6 cm and endometrial thickness of 17 mm on ultrasonography. She underwent endometrial biopsy to exclude endometrial cancer. The report of which came to be endometrial hyperplasia without atypia. Further MRI study confirmed the findings of USG of a complex cystic lesion of left adnexa 75 × 57 × 60 mm. Tumor marker for ovarian tumors were sent and inhibin B was found to be markedly raised. A provisional diagnosis of GCT (Granulosa cell tumour) was made and staging laparotomy was done. The uterus was found to be 12 × 8 cm size and a left sided ovarian cyst of 8-9 cm size with smooth wall and intact capsule was found. Patient had an uneventful postoperative recovery.